About adopting a systemic approach to design connected embedded systems: A MOOC promoting systems thinking and systems engineering. Issue 3 (7th October 2019) - Baron, Claude; Daniel‐Allegro, Brigitte
Abstract: A connected embedded system is a complex system that integrates hardware and software elements and has real‐time interactions with its environment. Developing such a system requires having a systemic approach, based on systems thinking and systems engineering (SE). Systems thinking demonstrates the need of adopting an interdisciplinary approach (not only technology focused but also considering societal or regulatory commitments), that is essential to explore the whole embedded systems field. SE enables learners acquiring a method which provides the means to set up a consistent design and management plan that fully integrates a product development. This paper describes how a MOOC has been designed and produced to promote the use of a systemic approach when developing connected embedded systems. The MOOC uses different case studies in order to progressively develop system thinker's skills for identifying and solving a variety of problems raised during the design of a connected embedded system. Launched in 2016, it attracted more than 10.800 learners in less than 2 years. What led to such a success is certainly because the team that created the MOOC experienced a collaborative and integrative approach, namely a systemic approach, that also revealed its benefits in this educative project.